Estimating Oxidation Rates of NOX and SO2 Released from Domestic Emission Sources in South Korea 국내 배출 NOX와 SO2의 대기 중 산화율 추정 - Kang, Yoon Hee; Kim, Soontae (Journal of Korean Society for Atmospheric Environment, 2022)
Nitrate (NO3 -) and sulfate (SO4 2-) are one of the main components of PM2.5 and are formed by atmospheric chemical processes of NOX and SO2, respectively. In this study, the Nitrogen Oxidation Ratio (NOR) and Sulfur Oxidation Ratio (SOR) of the air pollutants emitted from domestic emission sources in South Korea during the study period of 2019 were estimated to quantify how much domestic NOX and SO2 emissions are converted into nitrate and sulfate, respectively. To estimate the NOR/SOR, impacts of domestic NOX and SO2 emissions from the major source categories on PM2.5 were estimated using the Community Multi-scale Air Quality (CMAQ) - Brute Force Method (BFM) and Clean Air Policy Support System (CAPSS) 2016 emission inventory. The annual mean NOR and SOR were 0.083 and 0.085, respectively. During the seasonal PM management period (i.e., from January to March, and December), NOR was 0.02 higher than the annual average, however, SOR for the seasonal PM management period was 0.05 lower than the annual average. The annual average of NOR and SOR was lower than 0.1 in major metropolitan cities and/or the regions where large emission sources are located (e.g., Seoul metropolitan area and Ulsan) while they increased over downwind suburban or rural areas, such as Gyeongbuk, Jeju, and Gangwon. Among major 6 source sectors, production process that emits a large amount of NH3 emissions showed the highest annual mean NOR (0.233). In the combustion in manufacturing industries and production process, the SORs are both 0.099. While developing efficient and effective the emission reduction policy, it is recommended to take into account the seasonal, regional, and emission sectoral variations in the gas-to-particle conversion rates of NOX and SO2 as well as their impacts on PM2.5 concentrations.
Keywords: Emission; Gas-to-particle conversion rate; Nitrate oxidation ratio (nor); Pm2.5; Sulfur oxidation ratio (sor)